On Complete Convergence for Weighted Sums of ρ*-Mixing Random Variables - Aiting Shen; Xinghui Wang; Huayan Zhu (Abstract and Applied Analysis)
We prove the strong law of large numbers for weighted sums ∑i=1n‍aniXi, which generalizes and improves the corresponding one for independent and identically distributed random variables and φ-mixing random variables. In addition, we present some results on complete convergence for weighted sums of ρ*-mixing random variables under some suitable conditions, which generalize the corresponding ones for independent random variables.